Hybrid metaheuristics : 10th International Workshop, HM 2016, Plymouth, UK, June 8-10, 2016. Proceedings /: 10th International Workshop, HM 2016, Plymouth, UK, June 8-10, 2016. Proceedings. (2016) - Unknown
No abstract available